2016
DOI: 10.18632/oncotarget.9411
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of tensin2 enhances tumorigenicity and is associated with a variety of cancers

Abstract: Tensin family members, including tensin2 (TNS2), are present as major components of the focal adhesions. The N-terminal end of TNS2 contains a C1 region (protein kinase C conserved region 1) that is not found in other tensin members. Three isoforms of TNS2 have been identified with previous reports describing the shortest V3 isoform as lacking the C1 region. Although TNS2 is known to regulate cell proliferation and migration, its role in tumorigenicity is controversial. By gain-of-function overexpression appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 26 publications
(36 reference statements)
3
31
0
Order By: Relevance
“…Accordingly, we queried tissue microarrays from SHANGHAI OUTDO BIOTECH, which contains 84 gastric cancer samples, and found that SIRT2 was significantly increased in tumor tissues compared to adjacent tissues ( Figure 1 , A - C ). We queried the Kaplan-Meier plotter ( http://kmplot.com/analysis ) database [17] , [18] , which contains clinically annotated genomic data from gastric cancer samples, and found that high Sirt2 mRNA expression was associated with poor progression-free survival and overall survival (log-rank test) ( Figure 1 , D & E ). We further assessed the expression of SIRT2 in GC cell lines (AGS, HGC-27, MGC-803 and MKN-45) and normal gastric epithelial cells (GES-1) and found that the expression level of SIRT2 in GC cells was significantly higher than that of GES-1 cells ( Figure 1 F ).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, we queried tissue microarrays from SHANGHAI OUTDO BIOTECH, which contains 84 gastric cancer samples, and found that SIRT2 was significantly increased in tumor tissues compared to adjacent tissues ( Figure 1 , A - C ). We queried the Kaplan-Meier plotter ( http://kmplot.com/analysis ) database [17] , [18] , which contains clinically annotated genomic data from gastric cancer samples, and found that high Sirt2 mRNA expression was associated with poor progression-free survival and overall survival (log-rank test) ( Figure 1 , D & E ). We further assessed the expression of SIRT2 in GC cell lines (AGS, HGC-27, MGC-803 and MKN-45) and normal gastric epithelial cells (GES-1) and found that the expression level of SIRT2 in GC cells was significantly higher than that of GES-1 cells ( Figure 1 F ).…”
Section: Resultsmentioning
confidence: 99%
“…Tensin family members are known as focal adhesion proteins, and are known to be localized to focal adhesion in at least in some cell types [8]. in a podocyte cell line, the transfected full-length TNS2 displayed a peripheral dotted distribution pattern typical of a focal adhesion protein as in other cell types [2,9,14,31]. On the other hand, the distribution of the TNS2 ∆SH2-PTB in the podocyte cell line was distinct from that of the full-length TNS2; i.e., a focal adhesion protein.…”
Section: Discussionmentioning
confidence: 99%
“…Tensin 2 (TNS2) is a focal adhesion protein that regulates signaling pathways for cell shape and motility by bridging cytoskeleton and intracellular projections of transmembrane receptors. By acting as a protein tyrosine phosphatase, TNS2 dephosphorylates IRS1 reducing its activation for binding to signaling molecules and reduces Akt signaling via a negative feedback loop 39 . Centrosomal protein 57 (CEP57) mediates the mitogenic activity of fibroblast growth factor 2 (FGF2) which shows enhanced binding to senile plaques and neurofibrillary tangles and stimulates downstream signaling pathways (MAPK/ERK, PLC, Akt) 22,47,75 .…”
Section: Tgif1 Is Neuroprotective In Admentioning
confidence: 99%